2004
DOI: 10.1002/hep.20035
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of tumor necrosis factor-? in hepatic ischemia-reperfusion injury: Studies in tumor necrosis factor-? gene knockout mice

Abstract: Although hepatic ischemia-reperfusion (IR) injury is partially mediated by tumor necrosis factor-␣ (TNF), we recently found that low-dose TNF before IR is hepatoprotective. We examined the seemingly conflicting roles of TNF in mediating liver injury in a partial hepatic IR model using TNF gene knockout (TNF ko) mice to allow TNF replacement at specified times. Compared with wild-type mice, TNF ko mice exhibit minimal alanine aminotransferase release and few hepatonecrotic lesions during the early (time, 2 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
2
5

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(95 citation statements)
references
References 19 publications
3
85
2
5
Order By: Relevance
“…TNF Release During I/R Activates ASMase. TNF upregulation by activated Kupffer cells plays a key role in hepatic I/R injury, 5,6,23 and TNF-induced hepatocellular death is mediated in part through ASMase activation. 11,16 During I/R we detected an early release of TNF and postulated that this cytokine may contribute to I/R-induced ASMase activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TNF Release During I/R Activates ASMase. TNF upregulation by activated Kupffer cells plays a key role in hepatic I/R injury, 5,6,23 and TNF-induced hepatocellular death is mediated in part through ASMase activation. 11,16 During I/R we detected an early release of TNF and postulated that this cytokine may contribute to I/R-induced ASMase activation.…”
Section: Discussionmentioning
confidence: 99%
“…17,18,22 Previous studies using mice deficient in TNF gene or TNF receptor 1 (TNFR1) have identified TNF as a critical mediator in warm hepatic I/R injury. 5,6,23 Moreover, increased hepatic ceramide levels have been observed in cold ischemia and warm reperfusion, 24 although its consequences and regulation were not further examined. Furthermore, the regulation of SMases has been reported in a rat model of I/R, with NSMase being stimulated during the reperfusion of the ischemic liver, as opposed to ASMase, whose activity decreased.…”
mentioning
confidence: 99%
“…It was not clear why low-versus high-dose ASP had opposing effects in liver regeneration and injury in C3 -/-mice following PHx. However, while the complement activation products C3a and C5a have been shown to play a key role in the priming stages of liver regeneration via their effect on TNF-α and IL-6 expression, these cytokines can play dual roles in hepatocyte regeneration and injury, and increased and prolonged expression of these inflammatory cytokines is associated with hepatic injury (27)(28)(29). We therefore investigated the effect of high-versus low-dose ASP on TNF-α and IL-6 expression levels and on hepatic neutrophil infiltration (MPO activity) following PHx.…”
Section: Figurementioning
confidence: 99%
“…JNK is activated by environmental stresses such as oxidative stress (Mendelson et al, 1996), and also by cytokines, including TNF- (Liedtke et al, 2002) and IL-1 (Finch et al, 2001). These cytokines are considered to be major mediators in hepatic I/R injury (Kato et al, 2002;Teoh et al, 2004). JNK activation during reperfusion is believed to play a role in hepatocyte apoptosis (Marderstein et al, 2003;Uehara et al, 2004;Uehara et al, 2005).…”
Section: Introductionmentioning
confidence: 99%